The Effectiveness Of PC6 Point Acupressure In Overcoming First Trimester Degree Ii Hyperemesis Gravidarum - Indah Gasela; Ratna Dewi Putri; Stella Maris Bakara (Media Informasi, 2025)
Hyperemesis gravidarum is a severe complication in early pregnancy marked by excessive nausea and vomiting, often leading to dehydration, weight loss, and reduced maternal quality of life. Despite being frequently underestimated, this condition requires timely and effective management. One non-pharmacological intervention that has gained attention is acupressure at the PC6 (Nei Guan) point. This study aimed to evaluate the effectiveness of PC6 acupressure in reducing the frequency and intensity of hyperemesis gravidarum among first-trimester pregnant women. A quasi-experimental pretest-posttest design without a control group was conducted on 20 respondents at the Rahmawati Midwifery Clinic, Pangkalpinang. Participants performed acupressure therapy for five minutes, three times daily for seven consecutive days. Data on nausea intensity and vomiting frequency were collected before and after the intervention using a standardized scale and logbook. Results showed a significant decrease in nausea and vomiting symptoms, with the average score dropping from 8 (range 7–9) before therapy to 3 (range 2–4) after therapy. Statistical analysis using paired t-test yielded a p-value of 0.000, indicating a highly significant difference. These findings suggest that PC6 acupressure is an effective, simple, and low-cost complementary therapy for managing hyperemesis gravidarum in antenatal care services, particularly at the community level.